Coal Rank Variation Induced by Igneous Intrusion in Pit A, Tanjung Enim, South Sumatra - Dimas Kurnia Pratama; Dwi Vina Febrim; Harnani Harnani (Jambura Geoscience Review, 2026)
This study investigates the effect of igneous intrusion on coal quality variation in Pit A, PT Bukit Asam Tbk., Tanjung Enim, South Sumatra, with emphasis on calorific value (CV) as an indicator of coal rank alteration. The research utilized geological and coal quality data from nine exploration drillholes (DKP_01–DKP_09) intersecting four major coal seams (A1, A2, B, and C). The dataset included drilling records, geophysical logs (gamma ray and density), core descriptions, geological structure measurements, and proximate analysis results from coal samples located 70.9–1001.4 m from the interpreted intrusion body. Seam correlation and three-dimensional subsurface modeling were performed using Leapfrog software to evaluate spatial coal quality variation relative to intrusion proximity. The results indicate that coal located closer to the intrusion generally exhibits higher calorific values and fixed carbon content, accompanied by lower inherent moisture and volatile matter values, reflecting localized thermal alteration. Coal calorific values range from approximately 11,064 to 14,311 Btu/lb (GCV_MMMF) and show a general decrease with increasing distance from the intrusion. Spatial distribution mapping reveals a clear zonation pattern, with higher calorific values concentrated near the intrusion contact and lower values occurring farther from the heat source. Several anomalous values were identified and are interpreted to reflect local overheating effects and geological heterogeneity. Structural interpretation suggests that faults may have facilitated magma emplacement, although their direct influence on coal quality variation remains uncertain. Overall, the results indicate a strong spatial relationship between igneous intrusion proximity and localized coal rank enhancement within the study area.